2017
DOI: 10.1080/02713683.2017.1313429
|View full text |Cite
|
Sign up to set email alerts
|

Medial and Lateral Rectus Muscle Insertion Distance and Width in Esotropia and Exotropia Patients

Abstract: Insertion distances of the medial and LR muscles are not statistically different in ET, XT, and control patients. Only MR muscle width was affected by the size of the deviation in ET patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…The muscle insertion and its anatomy are important for understanding the physiology of eye movements. However, available anatomic studies on insertions of extraocular muscles especially in vivo measurements are very few [5, 6] and no study on AACE has focused on anatomic characteristics of extraocular muscles. Among all the extraocular muscles, Lai et al [5] found the insertion of the medial rectus seemed to be the most reliable and invariant of the rectus muscles in all patients regardless of their ethnic background.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The muscle insertion and its anatomy are important for understanding the physiology of eye movements. However, available anatomic studies on insertions of extraocular muscles especially in vivo measurements are very few [5, 6] and no study on AACE has focused on anatomic characteristics of extraocular muscles. Among all the extraocular muscles, Lai et al [5] found the insertion of the medial rectus seemed to be the most reliable and invariant of the rectus muscles in all patients regardless of their ethnic background.…”
Section: Discussionmentioning
confidence: 99%
“…Athavale et al [18] and Surawatsatien et al [19] found the distance of insertion of medial rectus to the limbus was 7.3 mm in Indian population and 5.7 mm in Thai population respectively from the measurement of cadavers. Lai et al [5] and Niyaz et al [6] measured the distance of medial rectus by a caliper in the esotropic and exotropic patients who underwent strabismus surgery and in the control group when a buckling surgery for retinal detachment was performed. Lai et al [5] found the distance from the insertion location to the limbus of medial rectus was 5.2 mm in the control group and 5.3 mm in the strabismus group in Taiwanese (Han Chinese) population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations